Agriculture, Nutrition, and Gender Linkages (ANGeL) evaluation results - Ahmed, Akhter; Hoddinott, John F.; Menon, Purnima; Quisumbing, Agnes R.; Roy, Shalini; Younus, Masuma; Ghostlaw, Julie; Haque, Md. Latiful; Hossain, Nusrat Zaitun; Parvin, Aklima; Quabili, Wahid; Tauseef, Salauddin; et al. (International Food Policy Research Institute, 2018)
The relationships between agricultural diversity, dietary diversity, and gender norms are complex and multi-dimensional. To better understand these links, and how to most effectively promote nutrition- and gender-sensitive agriculture in Bangladesh, the International Food Policy Research Institute (IFPRI) designed the Agriculture, Nutrition, and Gender Linkages (ANGeL) pilot project, implemented by the Ministry of Agriculture, Government of the People’s Republic of Bangladesh. ANGeL aimed to identify actions and investments in agriculture that will help increase farm household income, improve nutrition, and empower women. Using rigorous research, namely, a randomized controlled trial design, IFPRI assessed impacts of the ANGeL project interventions on various outcomes. Over the 17-month implementation period, with no inputs provided to participating farm households besides knowledge from trainings, ANGeL generated useful lessons on strengthening the agriculture-nutrition-gender nexus in the country. Both men and women benefited from agricultural trainings, yet women learned more from the same trainings. Crop diversity increased substantially in homestead gardens, mainly due to ANGeL’s emphasis on homestead food production from nutritious crops. Farmers also adopted improved production practices. We consistently found that women were more likely to apply knowledge gained from agricultural production trainings to adopt various types of improved agriculture production practices, such as pest disease and control, seed production and care, and use of quality fertilizer. Similarly, improvements in nutrition knowledge were far greater for women and when trainings were combined. These improvements in knowledge had impacts on nutrition outcomes, with increases in household diet quality and child dietary diversity over the project period. The strongest improvements in empowerment came when agriculture, nutrition, and gender sensitization trainings were combined. ANGeL’s household approach empowered women and men in unique ways: while women became more empowered in asset ownership and income decisions, men became more empowered in production and income decisions in select interventions. Attitudes related to gender of both women and men also improved, with more women recognizing that they make important contributions to their communities. ANGeL is the first ministry-led initiative that uses a rigorous impact evaluation to develop an evidence base to design and implement a national program. The ANGeL project is a significant step towards filling critical knowledge and action gaps in the country on promoting nutrition-and gender-sensitive agriculture.